Routine Outcome Monitoring (ROM) and Feedback: Research Review and Recommendations - Barkham, Michael; De Jong, Kim; Delgadillo, Jaime; Lutz, Wolfgang (Psychotherapy research, 2023)
To provide a research review of the components and outcomes of routine outcome monitoring (ROM) and recommendations for research and therapeutic practice. A narrative review of the three phases of ROM - data collection, feeding back data, and adapting therapy - and an overview of patient outcomes from 11 meta-analytic studies. Patients support ROM when its purpose is clear and integrated within therapy. Greater frequency of data collection is more important for shorter-term therapies, and use of graphs, greater specificity of feedback, and alerts are helpful. Overall effects on patient outcomes are statistically significant (g ≈ 0.15) and increase when clinical support tools (CSTs) are used for not-on-track cases (g ≈ 0.36-0.53). Effects are additive to standard effects of psychological therapies. Organizational, personnel, and resource issues remain the greatest obstacles to the successful adoption of ROM. ROM offers a low-cost method for enhancing patient outcomes, on average resulting in an ≈ 8% advantage (success rate difference; SRD) over standard care. CSTs are particularly effective for not-on-track patients (SRD between ≈ 20% and 29%), but ROM does not work for all patients and successful implementation is a major challenge, along with securing appropriate cultural adaptations.